The evolution of left ventricular assist devices—a moment to reflect - Kuehl, Michael; Garbade, Jens (Journal of Thoracic Disease, 2017)
In the Mechanical Circulatory Support Therapy with HeartMate 3 trial (MOMENTUM 3) Mehra et al. compared the outcomes of death and disabling strokes in 294 patients six months after implantation of the latest generation of left ventricular assist devices (HeartMate III) to patients treated with the former generation of the same manufacturer (HeartMate II, Thoratec/St Jude Medical) (1). The primary combined endpoint was survival free of disabling strokes or survival free of reoperations to replace or to remove the device at six months after implantation. No significant differences in mortality and disabling strokes were seen, but the rate of reoperations for malfunction was lower in the group of patients receiving the HeartMate III [1 (0.7%) vs. 11 (7.7%); hazard ratio: 0.08; 95% CI, 0.01 to 0.60; P=0.002]. The higher rates of reoperations were therefore the main driver not only for the statistically noninferiority, but also for the superiority of HeartMate III compared to HeartMate II for this particular outcome parameter. No events of suspected or confirmed thrombosis were reported in the HeartMate III group compared to 18 events in 14 (10.1%) patients treated with HeartMate II (P